Leave Approval System (LAS) / Mohd Nasrul Hakim Jalaludin - Mohd Nasrul Hakim , Jalaludin (2004)
Leave Approval System (LAS) is one of the main modules in e-Office project that offers also e-Transaction and Human Resources Management System (HRMS). LAS is a webbased client server system developed with the objectives of implementing the task of leave application and approval on a company or organizations. LAS proves that the possibility to deploy traditional client/server application on the internet.LAS allows staff I employee the ease of access to apply leave and allows manager to approve leave application easily. LAS consists to apply, to cancel, to approve and to calculate the number of leaves that have been design for both of the staff and administrator. LAS users are categorize to Board of Director (administrator) and Staff (employee). The administrators are allowed to enter all section in LAS. However, the employees are allowed to enter only one section (staffs page) by entering their user ID. LAS is developed by using FrontPage and Active Server Page (ASP), a client/server application development. lt is believed that LAS will gradually become an essential to every company and institutions in the future.